Epidemiology of Prostate Cancer in the Republic of Kazakhstan - Dariga SMAILOVA; Erlan OSPANOV; Meruert GAZALIYEVA; Dilyara KAIDAROVA; Oxana SHATKOVSKAYA; Zhanar ZAMANBEKOVA; Kuralay AMRENOVA; Tatyana BELIKHINA; Tasbolat ADYLKHANOV; Ardak OMARBEKOV; Marzhan DAULETYAROVA; Lyudmila PIVINA; et al. (Tehran University of Medical Sciences, 2019)
Background: The incidence and mortality from prostate cancer in most native Asian populations remain low although a gradual increase is observed over the last years. Methods: The statistical analysis of official data on prostate cancer mortality and morbidity was performed for the whole country and for Pavlodar Region. Results: The increase in the incidence of prostate cancer among the population of Kazakhstan is observed, which may be attributed to the introduction of screening program based on serum PSA. Still, the crude incidence rates in Kazakhstan are below world indices. Over the last few years, the decreasing prostate cancer mortality is observed that might be influenced by early diagnosis. The age-standardized incidence rates show that the majority of prostate cancer cases occur in advanced ages (70 years and older). Conclusion: More research is needed to determine the risk factors for prostate cancer, as well as ethnic and geographical trends for the population of Kazakhstan.